Does growth hormone-releasing factor assist follicular development in poor responder patients undergoing ovarian stimulation for in-vitro fertilization? - Howles, Colin M.; Loumaye, E.; Germond, M.; Yates, R.; Brinsden, P.; Healy, D.; Bonaventura, L.M.; Strowitzki, Thomas (Human reproduction, 1999)
Treatment with growth hormone-releasing factor (GRF) has been reported to improve the ovarian response to gonadotrophins in women who respond poorly to ovarian stimulation during in-vitro fertilization (IVF). The efficacy and tolerability of GRF were studied in a randomized, double-blind, placebo-controlled trial involving 196 patients.